Complementary therapies for people with motor neurone disease: extending a cancer care service. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Hughes, Philippa; Seymour, Lynn; Hollinger, Hannah; Evans, Jane; McDermott, Christopher; Shaw, Pamela
Abstract : Background: Cavendish Cancer Care (CCC) is a charitable organisation in Sheffield providing assessment, counselling and complementary therapies for people with cancer and their families. Motor Neurone Disease (MND), is characterised by progressive deterioration: muscle wasting, speech, swallowing, and breathing difficulties. A year-long pilot study for patients and carers, funded by South Yorkshire MND Association was set up using the CCC model of care, in conjunction with the MND Team at the Royal Hallamshire Hospital. We report here on patient experiences, using our standard evaluation procedures. Aim: To assess the value and outcomes of a supportive care service for people diagnosed with MND. Method: Data was collected over 1 year. Clients were seen at home or at the Centre, and completed the Measure Yourself Concerns and Wellbeing (MYCAW) scale, in which clients score their nominated main concerns on a 7-point scale at assessment, repeated at post-therapy review, and give comments on the service received. Results: Twenty-seven people, with ages ranging from 50 to 83, of whom 14 were men, used the service during the year. Fifteen were seen in their own homes, and twelve at the Centre. Physical symptoms were prominent among the concerns, along with emotional issues, the need for relaxation, for information, and for general wellbeing. Twenty-four patients received therapy: massage/aromatherapy massage, shiatsu and reflexology were chosen most often. Follow-up scores were available for 16 patients, with improvements in first nominated concerns for eleven, static scores for three and deterioration for two. Comments from those reporting no improvement suggest that there were benefits, but not specific to the concern, or transient. Conclusion: Compared to our usual cancer populations, patients with MND showed a higher proportion of symptom-based concerns. Improvement was reported by a smaller majority with MND compared to cancer patients. General benefits of the therapies were highlighted.